A systems approach to reducing maternal obesity: The Health in Preconception, Pregnancy and Postbirth (HIPPP) Collaborative. (30th June 2015) - Skouteris, Helen; Huang, Terry; Millar, Lynne; Kuhlberg, Jill; Dodd, Jodie; Callaway, Leonie; Forster, Della; Collins, Clare; Hills, Andrew; Harrison, Paul; Nagle, Cate; Moodie, Marj; et al.
<x xml:space="preserve">Abstract</x> Obesity in our childbearing population has increased to epidemic proportions in developed countries; efforts to address this issue need to focus on prevention. The Health in Preconception, Pregnancy and Postbirth (HIPPP) Collaborative – a group of researchers, practitioners, policymakers and end‐users – was formed to take up the challenge to address this issue as a partnership. Application of systems thinking, participatory systems modelling and group model building was used to establish research questions aiming to optimise periconception lifestyle, weight and health. Our goal was to reduce the burden of maternal obesity through systems change.